Weathering Characteristics of Flysch Rock Mass in Istria Peninsula, Croatia - Martina Vivoda Prodan; Zeljko Arbanas (Research Developments in Science and Technology Vol. 8, 2022)
Slope instability is caused by the slaking and weathering of weak rocks. Siltstones from flysch rock masses are highly susceptible to weathering, causing rapid changes in geotechnical characteristics and durability. The impacts of weathering on the engineering qualities of siltstone samples from flysch rock masses from the Istria Peninsula, Croatia, were examined in this study. Laboratory testing of siltstone samples of different weathering grades was conducted to determine their physical-mechanical properties, residual shear strength and uniaxial compressive strength, durability and mineralogical properties. The conventional slake durability index is inadequate for classifying the durability of weak rock types like siltstones. As a result, the fragment size distribution after each of five slaking cycles was used to determine the durability of siltstone samples of various weathering grades. The disintegration ratio was used to classify the tested samples, and the modified disintegration ratio was utilized to determine possible long-term degradation. The engineering qualities of different weathering grades of siltstones were established using laboratory tests. The results indicated significant influence of the weathering process on the plasticity, residual shear strength, uniaxial compressive strength, durability and mineralogical characteristics of the siltstones, thus affecting on the landslides and erosion processes in siltstones in the flysch zone in the Istria Peninsula, Croatia.